EXPLORING PUBLIC PERCEPTIONS OF FIRE RISKS IN RESIDENTIAL AND COMMERCIAL AREAS NEAR FUEL STATIONS IN GHANA - William, Daitey; Panin Kwame Baah, Owusu (Berajah Journal, 2025)
The hazardous fire conditions at fuel stations threaten both residential and commercial sectors of Ghana. This study evaluated community perceptions regarding fire risks in gas stations and it measured both preparedness and fire safety educational levels. The researchers employed triangulated data collection tools using unstructured interviews, focus group discussions and observations which collected data from citizens, business owner and gasoline station employees. Study findings showed general public awareness about fire hazards but inadequate people had preparedness measures alongside weak adherence to rules throughout the community. The insufficient planning of many fuel stations close to residential areas created additional fire hazards due to inadequate town development practices. The report supports updated zoning rules that need better law enforcement combined with enhanced fire safety education and fire risk reduction activities involving local communities. The improvement of fire emergency readiness requires the establishment of fire hydrants together with standardized safety drills and increased enforcement of fire safety legislation. The planned steps will establish safer workplace environments in Ghana together with reduced gas station safety hazards.